The Problem of Shortage of Foreign Language Training for Students During Professional Skills Development in the Field of Mechatronics; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Semykina I. Yu. Irina Yurievna (2015, 2015)
Title screen